Meaning and Philosophical Values of The Khanduri Maulod Tradition in Aceh Community (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This study aims to describe the meaning and philosophical values ​​of the khanduri maulod tradition in Acehnese society. This type of research is a qualitative research using an ethnographic approach. This research was conducted in Krueng Juli Timu Village, Bireuen District, Aceh Province. The informants in this study were Gampong Geuchiek, Gampong Imum, Youth Leaders, Members of the Aceh Traditional Council, and community leaders. Data collection techniques consist of observation, interviews and documentation. Data analysis techniques are carried out through; analysis, domain, taxonomic analysis, componential analysis, and analysis of cultural themes. The results of the research show that: 1) the values ​​contained in khanduri maulod include; religious values, social values, sincere values, mutual cooperation values, deliberation values, unity values, cultural values, and economic values, 2) the meaning contained in khanduri Maulod is a form of expression of love and affection for the Prophet Muhammad, S.A.W and establishing a relationship silaturrahmi between fellow villagers and invited guests. .